Understanding how students' relationships with their cellphones inform their experience of social participation online and offline - Oosthuizen, Jess (Rhodes University, Faculty of Humanities, Department of Psychology, 2015)
The pervasive presence of cellphones in the lives of urban young people around the globe has led to widespread research to evaluate the impact that this device has on young people's overall psychosocial development. This relationship is often characterised as "addictive" . This research study presents a unique South African youth perspective in a field of research that is predominantly conducted in the United States, Europe and Asia. It explores the relationship that students (ages 18"“21) at Rhodes University have with their cellphones in order to understand how this device informs their experience of social participation online and offline. Central to the design of this study is a "social media detox" which involved the research participants volunteering to restrict their social media and cellphone use for an agreed-upon period of time. The study employs interpretative phenomenological analysis (IPA) to uncover key themes from in-depth interviews before and after the detox. Eight respondents were interviewed twice; once before and once after their detox. This study provides insights into the integral role of a cellphone as reported from a young adult's perspective. Communicating on social media platforms using a cellphone has become normalised among this age-group and the respondents described how the cellphone feels like "a part of you" . Unlike interacting face-to-face which is potentially awkward and involves effort, socialising on a cellphone offers the respondents a sense of companionship, control and instant access to their peer groups. The respondents in this study seemed unaware of their own agency in social situations until their participation in the social media detox. By participating in this study, the participants became more aware of how their cellphone use influences social behaviour, both online and offline. The study proposes that the term "addiction" undermines the positive association young people have with their cellphones. Instead, this study suggests that "social fitness" would be a more relevant construct through which to encourage and support young people to exercise agency in their social lives. This exploratory study raises new questions for researchers, programme developers and educators to take up in future studies and programme development
Keywords: Cell phones -- South Africa -- Psychological aspects; Social participation; Cell phones -- South Africa -- Social aspects; College students -- South Africa; Social media addiction